Hard Carbon Nanosheets with Uniform Ultramicropores and Accessible Functional Groups Showing High Realistic Capacity and Superior Rate Performance for Sodium‐Ion Storage - Xia, Ji‐Li; Yan, Dong; Guo, Li‐Ping; Dong, Xiao‐Ling; Li, Wen‐Cui; Lu, An‐Hui (Advanced materials (Weinheim), 2020)
Hard carbon attracts considerable attention as an anode material for sodium‐ion batteries; however, their poor rate capability and low realistic capacity have motivated intense research effort toward exploiting nanostructured carbons in order to boost their comprehensive performance. Ultramicropores are considered essential for attaining high‐rate capacity as well as initial Coulombic efficiency by allowing the rapid diffusion of Na+ and inhibiting the contact of the electrolyte with the inner carbon surfaces. Herein, hard carbon nanosheets with centralized ultramicropores (≈0.5 nm) and easily accessible carbonyl groups (CO)/hydroxy groups (OH) are synthesized via interfacial assembly and carbonization strategies, delivering a large capacity (318 mA h g−1 at 0.02 A g−1), superior rate capability (145 mA h g−1 at 5.00 A g−1), and approximately 95% of reversible capacity below 1.00 V. Notably, a new charge model favoring fast capacitive sodium storage with dual potential plateaus is proposed. That is, the deintercalation of Na+ from graphitic layers is manifested as the low‐potential plateau region (0.01−0.10 V), contributing to stable insertion capacity; meanwhile, the surface desodiation process of the CO and OH groups corresponds to the high‐potential plateau region (0.40−0.70 V), contributing to a fast capacitive storage. Hard carbon nanosheets with centralized ultramicropores (≈0.5 nm), accessible functional CO/OH groups, and large graphitic layer spacings exhibit excellent sodium‐storage properties. The desodiation process from graphitic layers and CO/OH groups results in a new sodium‐storage characteristic with dual‐potential plateaus during the charge process, which favors a high output of 95%, realistic capacity, and rapidly capacitive sodium storage.